PENGARUH PEMBERIAN AMONIUM TIOSULFAT DAN KOMPOS TERHADAP SERAPAN EMAS (Au) TANAMAN AKAR WANGI (Vetiveria zizanioides) PADA TAILING JAMPANG KULON KABUPATEN SUKABUMI JAWA BARAT - Randy Prawira; S Syekhfani; Novalia Kusumarini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Artisanal Small Scale Gold Mining (ASGM) in Jampang Kulon produces tailing waste that contains heavy metals harmful to the environment. The taining, however, still contains gold metal (Au). Phytomining can be a solution in environmentally friendly gold mining by planting hyperakumulator plants on tailings and then extract its biomass. To increase the accumulation of gold in plant biomass, fertilizer is needed to enhance plants growth and chelate is necessary to increase the solubility of Au. This research aimed to know the effect of ammonium thiosulphate and compost on Au accumulation in vetiver grass (Vetiveria zizanioides L.) grown on tailings. This research used a completely randomized design with two factors, the dose of compost ; T0 (2.5 kg polybag-1), T1 (1.25 kg polybag-1), T2 (0 kg polybag-1) and the dose of ammonium thiosulphate ; K0 (0 g kg-1), K1 (5 g kg-1), K2 (10 g kg-1). The results showed that the addition of 10 g ammonium thiosulphate kg-1 significantly increased the accumulation of Au by 46% in plant roots and 35% in plant shoot related to control. While the addition of 1.25 kg compost polybag-1 could increase the accumulation of Au by 39% in plant roots.